Alterations in brain activation during cholinergic enhancement with rivastigmine in Alzheimer's disease. Issue 6 (1st December 2002) - Rombouts, S A R B; Barkhof, F; van Meel, C S; Scheltens, P
Abstract : Background: Rivastigmine enhances cholinergic activity and has been shown in clinical trials to decrease the rate of deterioration in Alzheimer's disease. It remains unclear where in the brain it exerts its effect. Functional magnetic resonance imaging (fMRI) can be used to measure changes in brain function and relate these to cognition. Objectives: To use fMRI to study brain activation with rivastigmine treatment. Methods: The effect on brain activation of a single dose of rivastigmine was tested in seven patients with mild Alzheimer's disease using fMRI during face encoding, and in five patients during a parametric working memory task. Results: During face encoding, rivastigmine increased bilateral activation in the fusiform gyrus. Brain activation was also enhanced in the prefrontal cortex in a simple working memory task. When working memory load was further increased, not only was increased activation seen, but in certain areas there was also decreased activation. Conclusions: These findings link the previously observed increase in cognitive performance in Alzheimer's disease after treatment with a cholinesterase inhibitor to altered brain activation. Although the results cannot be generalised to the Alzheimer's disease population at large, they provide evidence that in mild Alzheimer's disease, rivastigmine enhances brain activation in the fusiform and frontal cortices. This is compatible with the concept of cholinergic circuitry.